(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
The vehicle tracking system is increasingly present in the daily lives of companiesthat have their own fleet. This system is mostly used to monitor events that occur outsidethe companies. On the other hand, large companies that have heavy traffic of third-partyvehicles within their headquarters often do not have control over where these vehiclesare, which can characterize risks to the organization’s security and setbacks in receivinggoods. With this in mind, the article sought to present a vehicle tracking solution formonitoring third-party vehicles entering companies, through the development of a GPStracker capable of being temporarily fixed, which does not require coupling to thevehicle’s electrical system, and that provides position information, and with control rulesso that a given vehicle does not enter restricted areas. With that, a functional prototypethat verifies if the vehicle to which the tracker is connected has entered any areanotallowed, and if so, reporting the situation via email. The device developed was able todemonstrate effectiveness, correctly signaling the entry and exit of pre-determined areasof interest.